Release Profile of bisphosphonates risedronate using hydrogels as a carrier - Dr.drg. Tita Ratya Utari, Sp.Ort (UGM Scientific Meeting, 2014)
to discover release profile of bisphosphonate risedronate using gelatin hydrogels as carrier compared witn no carrier.